Reducing of Hydrogen Peroxide Effects by Pomegranate Peel Extract in Vivo, in Female Wistar Rats - Dhuha Salah Noori; Agharid. A.Al-Rasheed; Muna Salah Rasheed; Bashiru Garba (Institute of Medico-legal Publications Pvt Ltd, 2021)
In this study, the effect of pomegranate peel aqueous extract (PPEA) in reducing toxicities associated withhydrogen peroxide consumption was investigated using rats. This was achieved by assessing the serumbiochemical parameters as well as histopathological analysis of the liver and stomach sections. Forty,6-week-old female Wistar albino rats weighing 11.6± 4.4 g were divided equally into six groups. The ratswere administered the pomegranate extract and challenged with H2O2 via the oral route for 28 days. Toachieve this, positive control rats ingested H2O2 at 5 mg/ 100g body weight (b.w), while the negative controlgroups were given saline solution. Rats in the other three experimental groups were given H2O2 and treatedwith PPEA at 20, 40 mg and Vitamin at 25mg per 100g body weight respectively.H2O2 at 5 mg/100 g b.winduced injury to the liver and stomach tissues, while increasing levels of malondialdehyde (MDA), theAspartate Transaminase (AST) besides Alanine Transaminase (ALT) and, reduced of Glutathione GSH)were observed in comparison with the control groups. Treatment with PPEA demonstrated protective effectsby reducing the MDA, ALT and AST values and increase of GSH level as well as, improving the liver andstomach tissues to recover. Our results indicate that the administration of treatments against H2O2 usingPPEA decrease the harmful effect orally administered H2O2 at 5 mg/100g b.w.